A comparative study of hyperelastic constitutive models for an automotive shaft seal material. (2018) - Tobajas, Rafael; Elduque, Daniel; Javierre, Carlos; Ibarz, Elena; Gracia, Luis
The use of thermoplastic elastomers has increased strongly in recent decades in order to improve the manufacturing of numerous components within the machinery construction and automotive industry. The high manufacturing costs for this type of materials require a careful design phase in order to the final product can be according with the required specifications. One of the most important challenges that engineers face when designing with this type of materials is the simulation of mechanical behaviour using numerical methods. This task is not always easy since these materials often have a strongly nonlinear behaviour. In this work, a thermoplastic elastomer material has been analysed and an automotive component has been studied by means of five numerical simulations with five different constitutive models of material. This study shows that a careful selection of the constitutive model must be made to obtain reliable results since although several constitutive models fit well with the experimental data of the uniaxial and planar extension tests, when used in real components, there are significant differences in the obtained results.